Volume 2: Combustion, Fuels and Emissions, Parts a and B 2010
DOI: 10.1115/gt2010-23135
|View full text |Cite
|
Sign up to set email alerts
|

CH*/OH* Chemiluminescence Response of an Atmospheric Premixed Flame Under Varying Operating Conditions

Abstract: In this work the relationship between the ratio of the global CH* and OH* flame chemiluminescece and the global equivalence ratio of a technically premixed swirl-stabilized flame is investigated. The burner allows for a modification of the premix fuel injection pattern. The global flame chemiluminescence is monitored by a high-sensitivity light spectrometer and multiple photo-multipliers. The photo-multipliers were equipped with narrow optical band-pass filters and recorded the flame’s OH*, CH* and CO2* chemil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 3 publications
1
33
0
4
Order By: Relevance
“…Muruganandam et al [26] have shown that the CH ⁄ /OH ⁄ signal ratio for turbulent jet flame, swirl dump combustor, and gas turbine simulator exhibit the same trend and similar value for equivalence ratios between 0.65 and 0.95. Other researches have reached similar conclusions on the trend of CH ⁄ /OH ⁄ ratio (or OH ⁄ /CH ⁄ ) in swirl burners [27][28][29]. Muruganandam et al [28] have shown that the CH ⁄ /OH ⁄ ratio remains almost the same for Reynolds numbers in the range of 11,700 and 23,300.…”
Section: Equivalence Ratiomentioning
confidence: 63%
See 1 more Smart Citation
“…Muruganandam et al [26] have shown that the CH ⁄ /OH ⁄ signal ratio for turbulent jet flame, swirl dump combustor, and gas turbine simulator exhibit the same trend and similar value for equivalence ratios between 0.65 and 0.95. Other researches have reached similar conclusions on the trend of CH ⁄ /OH ⁄ ratio (or OH ⁄ /CH ⁄ ) in swirl burners [27][28][29]. Muruganandam et al [28] have shown that the CH ⁄ /OH ⁄ ratio remains almost the same for Reynolds numbers in the range of 11,700 and 23,300.…”
Section: Equivalence Ratiomentioning
confidence: 63%
“…They also showed that their swirl combustor data agrees favorably well with high pressure premixed laminar flame results [18]. Guyot and Lacarelle [29] measured the CH ⁄ /OH ⁄ ratio for Alstom EV-10 burner. They concluded that this ratio depends exponentially on the equivalence ratio and is independent of the air mass flow.…”
Section: Equivalence Ratiomentioning
confidence: 73%
“…Specifically, the chemiluminescence of OH ⁄ is a technique widely used in combustion investigation [14,16,15], in which OH ⁄ radicals are emitted when they decay at their ground state and the generated luminescence can be captured to several diagnostics as the detection of high-temperature regions or estimations of the equivalence ratio [19]. In this connection, before going further in the technique explanation, it is pertinent to define the ignition parameter that was characterized in this work using OH ⁄ chemiluminescence method: the lift-off length.…”
Section: Oh ⁄ Chemiluminescencementioning
confidence: 99%
“…This technique has been also employed for ignition delay measurements under the knowledge of the light intensity characteristics of each combustion phase [14,15]. Furthermore, several authors have underlined the effect of air-fuel mixture on soot formation, which can be associated with lift-off length [16][17][18][19]. It has been determined that ambient oxygen concentration rises products effective temperature, which continues increasing reactant temperatures and consequently reducing the ignition delay time [20].…”
Section: Introductionmentioning
confidence: 98%
“…It appears interesting to take into consideration as the CH*/OH* ratio, which is related to the flame's global heat release [38], decreases of 30% lowering the fuel/air equivalence ratio from 0.35 to 0.22.…”
Section: Flame Characterization and Instability Detection By Chemilummentioning
confidence: 99%